Improved Neural Processing Efficiency in a Chronic Aphasia Patient Following Melodic Intonation Therapy: A Neuropsychological and Functional MRI Study - Tabei, Ken-ichi; Satoh, Masayuki; Nakano, Chizuru; Ito, Ai; Shimoji, Yasuo; Kida, Hirotaka; Sakuma, Hajime; Tomimoto, Hidekazu (Frontiers in Neurology, 2016)
Melodic intonation therapy (MIT) is a treatment program for the rehabilitation of aphasic patients with speech production disorders. We report a case of severe chronic non-fluent aphasia unresponsive to several years of conventional therapy that showed a marked improvement following intensive nine-day training on the Japanese version of MIT (MIT-J). The purposes of this study were to verify the efficacy of MIT-J by functional assessment and examine associated changes in neural processing by functional magnetic resonance imaging. MIT improved language output and auditory comprehension, and decreased the response time for picture naming. Following MIT-J, an area of the right hemisphere was less activated on correct naming trials than compared to before training but similarly activated on incorrect trials. These results suggest that the aphasic symptoms of our patient were improved by increased neural processing efficiency and a concomitant decrease in cognitive load.